Retrospect and prospect: development of China's economics in the past 70 years. Issue 2 (2nd December 2019) - Shi, Jinchuan; Jianliang, Ye
Abstract : Purpose: In the past 70 years since the founding of the People's Republic of China, China's economic studies have been constantly centered on major issues such as national modernization, social economic development and the establishment, reform and improvement of socialist economic system. The paper aims to discuss this issue. Design/methodology/approach: It has experienced a process of transition from the establishment of traditional Soviet's paradigm of political economics to that of modern economics, during which drastic changes have been observed in various aspects of China's economics, including research content, scope and methods. Findings: Based on that, a discipline system of economics in line with international economics has been initially established. Currently, under the guidance of Marxism, scholars in China's economics actively draw on the beneficial knowledge system and analytical methods from modern economics, emancipate their minds, seek truth from facts and constantly fortify confidence in the socialist path, theory, system and culture, continuously enhance the discourse power of China's economics in global economic governance system, so as to push forward to the building of a theoretical system of socialist economics with Chinese Characteristics in the new era. Originality/value: Economics is a discipline that studies resource allocation and human's behavior of making a choice based on rationality. Emerged in the industrial revolution and developed in the exploration of a large-scale socialized mode of production and resource allocation system, this discipline has gradually become a broadly explanatory force in social sciences which profoundly affects the economic decision-making behaviors of the government and various economic entities.